123k views
14 votes
X+y=2 x-y=4 substitution

User Thar
by
4.9k points

2 Answers

8 votes

We have following two given equations which are:


\implies\sf{x + y = 2 \: ...(1)}


\implies\sf{x - y = 4}


\implies\sf{x = 4 + y \: ...(2)}

Now replacing the value of x of equation (2) in equation (1),


\implies\sf{x + y = 2}


\implies\sf{4 + y + y = 2}


\implies\sf{4 + 2y = 2}


\implies\sf{2y = 2 - 4}


\implies\sf{2y = - 2}


\implies\sf{y = ( - 2)/(2) }


\implies\sf{y = - 1}

Now replacing y = -1 in equation (1),


\implies\sf{x + y = 2}


\implies\sf{x + ( - 1) = 2}


\implies\sf{x - 1 = 2}


\implies\sf{x = 2 + 1}


\implies\sf{x = 3}

  • The values of x and y are 3 and -1
User Kartavya Ramnani
by
4.7k points
8 votes

Answer:

x = 3

y = -1

Explanation:

x + y = 2 ---------------------(I)

x -y = 4

x = 4 + y -----------------(II)

Substitute x = 4 + y in equation (I)

4 + y + y = 2

4 + 2y = 2

Subtract 4 from both sides

2y = 2 - 4

2y = - 2

Divide both sides by 2

y = -2/2

y= -1

Substitute y = -1 in equation(II)

x = 4 - 1

x = 3

User Joensson
by
5.1k points